The accountability priorities of Australian Parliamentarians - Mulgan, Richard (2008)
Managerialist reforms to the public service, as part of the drive for improved efficiency and effectiveness, sought to reorient the accountability priorities of parliamentarians away from a supposedly excessive concern with process and results and more towards results (outputs and outcomes). To what extent, if any, have the accountability priorities of parliamentarians changed over the last two decades? Content analysis of a sample of estimates committee hearings dealing with six departments over three selected years (1986, 1992 and 2003) reveals a marked increase in attention to outputs and a correspondingly decreased focus on inputs (with little change in concern for process), thus confirming a managerialist trend. At the same time, Senators' explicit references to departments' budget documentation and annual reports fell away noticeably with the introduction of the outcomes and outputs framework which is therefore failing their accountability needs. - Reproduced.
Keywords: Legislators - Australia; Australia. Parliament; Parliament